When the sea turned to silver - Lin, Grace (New York ; Boston : Little, Brown and Company, 2016)
"Pinmei, a storyteller's granddaughter, must find the Luminous Stone that Lights the Night to rescue her grandmother, who has been kidnapped by the Tiger Emperor"--
Companion book to: Where the mountain meets the moon.
Includes bibliographical references.
Keywords: Adventure stories; Kidnapping -- Fiction; Grandmothers -- Fiction; Storytellers -- Fiction; Fairy tales; China -- History -- Fiction; Quests (Expeditions.); Kidnapping; Kidnapping -- Fiction; Fairy tales; Grandmothers; Adventure and adventurers -- Fiction; JUVENILE FICTION -- Fairy Tales & Folklore -- Adaptations; JUVENILE FICTION -- Fantasy & Magic; JUVENILE FICTION -- Historical -- Asia; China; Quests (Expeditions) -- Juvenile fiction; Fantasy fiction; Action and adventure fiction; History; Fiction; Juvenile works; Fairy tales